A perioperative multidisciplinary care bundle reduces surgical site infections in patients undergoing synchronous colorectal and liver resection. Issue 2 (February 2019) - Tufts, Lauren S.; Jarnagin, Emma D.; Flynn, Jessica R.; Gonen, Mithat; Guillem, Jose G.; Paty, Philip B.; Nash, Garrett M.; Smith, Joshua J.; Wei, Iris H.; Pappou, Emmanouil; D'Angelica, Michael I.; Allen, Peter J.; et al.
Abstract: Background: Surgical site infections (SSIs) are a major cause of morbidity, mortality, and healthcare costs, and patients undergoing simultaneous colorectal/liver resections are at an especially high SSI risk. Methods: Data were collected on all patients undergoing synchronous colorectal/liver resection from 2011 to 2016 (n = 424). The intervention, implemented in 2013, included 13 multidisciplinary perioperative components. The primary endpoints were superficial/deep and organ space SSIs. Secondary endpoints were hospital length of stay (LOS) and 30-day readmission rate. To control for changes in SSI rates independent of the intervention, interrupted time series analysis was conducted. Results: Overall, superficial/deep, and organ space SSIs decreased by 60.5% (p < 0.001), 80.6% (p < 0.001), and 47.6% (p = 0.008), respectively. In the pre-intervention cohort (n = 231), there were 79 (34.2%), 31 (13.4%), and 48 (20.8%) total, superficial/deep, and organs space SSIs, respectively. In the post-intervention cohort (n = 193), there were 26 (13.5%), 5 (2.6%), and 21 (10.9%) total, superficial/deep, and organs space SSIs, respectively. Median LOS decreased from 9 to 8 days (p < 0.001). Readmission rates did not change (p = 0.6). Interrupted time series analysis found no significant trends in SSI rate within the pre-intervention (p = 0.35) and post-intervention (p = 0.55) periods. Conclusion: In combined colorectal/liver resection patients, implementation of a multidisciplinary care bundle was associated with a 61% reduction in SSIs, with the greatest impact on superficial/deep SSI, and modest reduction in LOS. The absence of trends within each time period indicated that the intervention was likely responsible for SSI reduction. Future efforts should target further reduction in organ space SSI.